PEMANFATAAN SISA OLAHAN MINYAK KELAPA “TAIMINYA” GUNA MENJAWAB MASALAH PANGAN DAN EKONOMI DI DESA LATUHALAT, KOTA AMBON - Jusuf Leiwakabessy; Ronald Darlly Hukubun; Sherly Lewerissa; Laura Bianca Silvia Huwae; Laury Marcia Chara Huwae (Jurnal Abdimas Bina Bangsa, 2023)
Coconut is a plant and natural potential that is excellent in Latuhalat Village. Coconut has so many benefits that it has earned the nickname the tree of life because every part of it can be used for the benefit of society. Coconut processing in Latuhalat Village is carried out on a small and traditional scale, namely processing it into coconut cooking oil. This processed product will leave processed waste (processed waste) known as "taiminya". This processed residue is usually not used anymore, then thrown away or used as animal feed. The Pattimura University PKM Team presents innovation and development of taiminya into "taiminya confectionery" and "taiminya chili sauce" products. This innovative product is expected to increase the income of the people of Latuhalat Village